A GOBICONODONTID (MAMMALIA, EUTRICONODONTA) FROM THE EARLY CRETACEOUS (BARREMIAN) WESSEX FORMATION OF THE ISLE OF WIGHT, SOUTHERN BRITAIN - Sweetman S.C. (My University, 2006)
Bulk screening of Early Cretaceous (Barremian) strata of the Wessex Formation, exposed in sections on the south-west and south-east coasts of the Isle of Wight, southern England, has resulted in the recovery of mammal remains, the first to be obtained from Wealden Group strata since the early 1970s. The fauna comprises at least six taxa represented by isolated teeth and in addition, in the case of an as yet undescribed spalacotheriid, a partial dentary. One of the teeth, a distal premolar, is of unique tricuspid, single-rooted morphology and represents the first British record of the Gobiconodontidae. Discovery of a gobiconodontid mammal in Early Cretaceous deposits of Britain sheds further light on the palaeogeographical distribution of an apparently successful clade of Early Cretaceous mammals and together with the occurrence of a gobiconodontid in the earliest Cretaceous of North Africa calls into question recent hypotheses concerning the area of origin of the Gobiconodontidae and mechanisms of dispersal therefrom. © 2006 The Palaeontological Association.
Keywords: BRITAIN; CRETACEOUS; GOBICONODONTIDAE; MAMMALIA; PALAEOGEOGRAPHY; PREMOLAR; Mesozoic::Cretaceous::Lower::Barremian; Мезозой::Меловая::Нижний::Барремский